The Challenges and Strategies in English Communication of UNNES 7th Semester Students during International Community Service Program (ICSP) Participation - Shafa Maria Hanurani Putri; Girindra Putri Dewi Saraswati (Borneo Educational Journal (Borju), 2026)
This paper focuses on revealing the challenges in English communication of UNNES 7th semester students during the International Community Service Program, as well bridging unexpected cultural gaps in communication, analyzed beyond the classroom-based context to extends existing discussion on communication competence. This paper adopts a qualitative descriptive approach, with 7 participants involved. Data collection was initially conducted with an open-ended questionnaire, followed by participants being invited back for a semi-structured interview. The findings revealed the main communication challenges faced by participants, such as limited knowledge of English vocabulary, and the challenge of understanding the English accent of Malaysians. However, several strategies in overcoming communication challenges were implemented, including the use of fillers, appeal for help strategy, applying code-switching, and the use of body gesture strategy. This paper presents opinions and experiences of the participants involved, highlighting the challenges of English communication in international scope and the strategies applied. In addition, this paper suggests the necessity of exposure to English learning in real-life contexts, such as involved in international standard programs to enhance long-term communication skills